DEVELOPMENT OF FINANCIAL REHABILITATION OF ENTERPRISES (World Bulletin of Management and Law, 2024)
An article is devoted to theoretical and practical aspects of financial rehabilitation of enterprises. Different approaches of economists to the essence and meaning of the concept of “financial rehabilitation of the enterprise” are analyzed. In the form of a graphic interpretation, the main tasks included in the financial rehabilitation of the enterprise, as well as the algorithm of methods for its implementation, are presented. A number of problems that may arise in the process of financial rehabilitation of enterprises are identified and substantiated. Among them, the most important is the cost of this process, as well as the lack of effective methods and specialists for diagnosing the financial state of the enterprise.